2003
DOI: 10.1097/00001756-200303030-00013
|View full text |Cite
|
Sign up to set email alerts
|

NADPH-diaphorase-positive neurons in the auditory cortex of young and old rats

Abstract: Age-related changes in NADPH-diaphorase (NADPH-d)-positive neurons were examined in the auditory cortex of young (3 months old) and very old (36 months old) rats (strain Long Evans). In very old rats a significant reduction was found in the thickness of the auditory cortex, to 54% of that in young animals, as well as changes in the shape and configuration of nerve cell bodies and dendrites. Quantitative analysis demonstrated an age-related increase in the number of dendritic segments and dendritic branching po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
21
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(23 citation statements)
references
References 0 publications
2
21
0
Order By: Relevance
“…In contrast, a substantial decrease with aging in the levels of other markers in the auditory cortex of rats was reported in the case of GABA (Ling et al 2005), NADPH-diaphorase (Ouda et al 2003) and acetylcholine (Stemmelin et al, 2000). In our study we evaluate age-related…”
Section: Introductionmentioning
confidence: 86%
“…In contrast, a substantial decrease with aging in the levels of other markers in the auditory cortex of rats was reported in the case of GABA (Ling et al 2005), NADPH-diaphorase (Ouda et al 2003) and acetylcholine (Stemmelin et al, 2000). In our study we evaluate age-related…”
Section: Introductionmentioning
confidence: 86%
“…Idrizbegovic et al [2006] also showed a 25% reduction in the neurons in the dorsal and ventral cochlear nucleus in 24-month-old mice. Moreover, Ouda et al [2003] found a 46% reduction in the thickness of the auditory cortex in 36-month-old rats compared to in 3-month-old rats. Our study also found fewer neurons in the auditory cortex in old C57BL/6J mice than in young mice, but the number of apoptotic neurons was much higher than in young mice.…”
Section: Discussionmentioning
confidence: 85%
“…Few neuronal morphometric changes were observed, and only in specific bregma levels of Te2 and Te3, which makes difficult to draw conclusions from them. Nevertheless, the increase in the number of dendrites has been said to represent compensatory mechanisms related to the reduction in cortical NADPH-d-positive neurons (Ouda et al, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…In central auditory structures, NOS activity was found in neuronal elements of the cochlea (Fessenden et al, 1994), superior olivary complex (Reuss, 1998;, inferior colliculus (IC) (Druga and Syka, 1993), and auditory cortex (AC) (Druga and Syka, 1993;Huh et al, 1998;Ouda et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation